COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF INDIVIDUAL BALLISTIC PROTECTION MEANS USED IN THE RUSSO-UKRAINIAN WAR: COMPARATIVE ANALYSIS OF THE EFFECTIVENESS OF INDIVIDUAL BALLISTIC PROTECTION MEANS USED IN THE RUSSO-UKRAINIAN WAR - Dimitrov, Miroslav; Conev, Conyu (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
The present scientific paper presents a comparative analysis of the different types of individual ballistic protection devices, particularly focusing on body armor used in the high-intensity conflict between Russia and Ukraine. With the advancement of technologies and the introduction of new tactics in modern conflicts, losses of personnel significantly increased. The use of effective individual ballistic protection devices substantially reduces these losses. The report examines the following parameters to compare different types of body armor: class of ballistic protection, weight, protective area, and comfort in use. To conduct the analysis, available literary sources, military reports, and feedback from the personnel of the countries involved in the conflict were studied.